Using GDPR to improve legal clarity and working conditions on digital labour platforms: Can a code of conduct as provided for by Article 40 of the General Data Protection Regulation (GDPR) help workers and socially responsible platforms? - Michael Silberman; Hannah Johnston (European Trade Union Institute (ETUI), 2020)
This paper examines how the General Data Protection Regulation (GDPR) can be used to address procedural problems faced by platform workers, including opaque rating systems, arbitrary account suspension and nonpayment, and uncommunicative clients and platform operators. GDPR provides workers with a variety of rights with respect to their data, including right of access, right to rectification, and rights regarding automated decision-making. Additionally, Art. 40 of the GDPR establishes the possibility for groups of controllers to develop codes of conduct that clarify the application of GDPR to their particular sectors. This paper details the application of GDPR to labor platforms, provides draft text for an Art. 40 code of conduct for labor platforms, and discusses how such a code could help address procedural problems encountered by platform workers.This paper can help spark a discussion at European level among trade unions and other stakeholders in platform work about how to use GDPR to address the 'procedural problems' faced by platform workers, regardless of their employment status.
Keywords: 330; Data protection; telework; Working conditions; EU countries; Datenschutz; Telearbeit; Arbeitsbedingungen; EU-Staaten